A novel CLAVATA1 mutation causes multilocularity in Brassica rapa. (6th January 2023) - Chow, Hiu Tung; Kendall, Timmy; Mosher, Rebecca A.
Abstract: Locules are the seed‐bearing structure of fruits. Multiple locules are associated with increased fruit size and seed set, and therefore, control of locule number is an important agronomic trait. Locule number is controlled in part by the CLAVATA‐WUSCHEL pathway. Disruption of either the CLAVATA1 receptor‐like kinase or its ligand CLAVATA3 can cause larger floral meristems and an increased number of locules. In an EMS mutagenized population of Brassica rapa, we identified a mutant allele that raises the number of locules from four to a range of from six to eight. Linkage mapping and genetic analysis support that the mutant phenotype is due to a missense mutation in a CLAVATA 1 ( CLV1 ) homolog. In addition to increased locule number, additional internal gynoecia are formed in brclv1 individuals, suggesting a failure to terminate floral meristem development, which results in decreased seed production.